Faktor Resiko Hipertensi Pada Anak Buah Kapal (ABK) Yang Terpapar Kebisingan Di Direktorat Polisi Perairan, Polda Aceh - Kiki Rezeki Amelia; Muhammad Iqbal S; Nia Hairu Novita (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypertension is a Non Communicable Disease (NCD) as a risk factor for myocardial infarction, stroke, acute renal failure and the world's number one cause of death, also dubbed The Silent Killer. The prevalence of hypertension will continue to increase sharply and predicted in 2025 as many as 29% of adults around the world are exposed to hypertension. Noise can affect the health of body functions that cause an increase in blood pressure and the form of increased body sensitivity such as the increased cardiovascular system in the form of increases in blood pressure and increased pulse Heart. This research is quantitative analytic with cross sectional type of approach. The samples in this study were 220 Water Police of the Directorates in Banda Aceh. Samples were taken from 12 ship which has average level of noise is 141.25 dBA determined by purposive sampling. Test statistics using Chi Square Test. The results of the research shows that the prevalence of hypertension in the crew man at the Directorates of Water Police in 2019 is 71,36%. Statistical results of bivariate statistics on risk incidence of hypertension stress work with P-value = 0.001. The most dominant risk factor for hypertension is the stress work have the risk of hypertension. It is hoped that the water police of Banda Aceh, in addition to encouraging medical check-up programs every 2 times a year to provide information and education about the importance of maintaining a healthy lifestyl and exercise routine. For the Directorates of water police of Polda Aceh need to do regulations on the crew man to avoid sedentary hypertension.